University–industry collaboration within the triple helix of innovation: The importance of mutuality. (8th December 2017) - Jackson, Paul; Mavi, Reza Kiani; Suseno, Yuliani; Standing, Craig
Abstract: This article was triggered by the observation that not only are there very low rates of collaboration between Australian firms and universities, but that there are similarly low rates of collaboration between Australian firms, their clients and suppliers. This suggests that the lack of collaboration with universities may be caused by something within the firm context, rather than specific difficulties in the relationship between firms and universities. Using OECD data, we found a general correlation between firm–firm collaboration and firm–university collaboration. After cluster analysis of national collaboration rates, we compared Australia with the UK. We found the most significant variation in collaboration occurs within the dimension of mutuality: what is to be gained by both parties. Mutuality is most common within a diverse economy with complex manufacturing and supply chains, and consequently higher levels of knowledge intensity. Our results suggest these are the key differences in driving collaboration for innovation.